Leadership Strategies in Optimizing Digital Interactive Boards through the Peer Tutoring Model in Elementary Schools: A Literature Review - Nunik Setyowati; Siti Mas’ula; Oktaviani Adhi Suciptaningsih; Riska Pristiani; Slamet Arifin (Universitas Negeri Makassar, 2026)
This study aims to analyze the leadership strategy of school principals in optimizing Digital Interactive Boards through the peer tutor model in elementary schools. The research method used in the literature study is to review ten relevant scientific articles that are related to educational leadership, learning technology, or peer tutoring. The data analysis technique used is content analysis by examining the content of scientific articles that have been collected, then identifying concepts, findings, and information that are relevant to the focus of the research. The results of the study show that the leadership of school principals is a determining factor in the success of the optimization of Digital Interactive Boards, with three main effective strategies, namely modeling, creating opportunities, and promoting. The peer tutoring model has proven to be effective as a professional development approach because it builds trust, is collaborative, and responsive to the specific needs of teachers. The success of this model depends on the ability of school principals to create a collaborative culture through teacher empowerment, administrative restructuring, and delegating responsibility to teachers with superior competencies. The optimization of Digital Interactive Boards is not only determined by the technical aspects, but especially by the pedagogical qualities in their use to create student-centered interactive learning. This research implies the need for policy support from the government and technology leadership training for school principals to facilitate the sustainable implementation of the peer tutor model.